Financial Stability of Trade Sphere Companies as a Precondition to Their Development: Conclusions for Financial Support (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Considering the generalized methodological basis for evaluation of trade sphere companies’ financial stability, the article contains the analysis of financial stability current status and dynamics, being based on the assumption that financial stability of business entities is a dominant factor in determining possibilities for their development and success. Negative indication values of the owner capital and own working capital reflect critical financial status of trade sphere companies. Further calculations and analysis of the indications of trade sphere financial stability showed that during the whole period of the research they were considerably below the economically viable level. Based on the calculated data, we could prove financial stability of the sphere to be insufficient, as well as witness deformation of its financial-economical system and lack of financial support.
Keywords: development of trade, financial stability, financial security, equity, own working capital